Comparison of two methods in estimating the relation between dental age and chronological age - Surya Gunasekaran; Nazargi Mahabob; Captain S Elangovan; Suman Jaishankar; B Senthil Kumar; Deepika Rajendran (Wolters Kluwer Medknow Publications, 2021)
Introduction: Personal identification is becoming increasingly important not only in legal medicine but also in criminal investigation, identification, and genetic research. Dental age (DA) estimation has gained acceptance because it is less variable when compared to other age indicators. Aim: This study aims to determine DA by radiographic methods in digital orthopantamogram using Willem's method and in intraoral periapical radiograph using Kvaal's method and also to find out the accuracy of two methods in determining the relation between DA and chronological age. Materials and Methods: The study sample consisted of 75 randomly selected subjects who referred to the Oral Medicine and Radiology department for the purpose to undergo orthodontic treatment, were selected. Orthopantmograph and one intraoral periapical radiograph of right mandibular first molar using paralleling cone technique were taken for each patient The DA was determined using orthopantamography by Willem's method and intraoral periapical radiograph by Kvaal's method. Results: The student's t-test was used to analyze the significance between the two different age estimation methods. In Demirjian's method, the overall mean difference between estimated DA and CA for males was 15.10 years, while for females was 11.88 years. Estimated DA assessment by Willem's method appeared to underestimate chronological age both in males and females. Conclusion: In this study, a significant relation was found between estimated DA and CA in the Willem method (p-0.00) and Kvaal's method (p-0.05). Both the methods seem to be applicable in estimating the age of both genders.